2017
DOI: 10.2166/nh.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Lithuanian river runoff, temperature and their extremes under climate change

Abstract: The aim of this research is to analyse and project the effects of changing climate on Lithuanian river runoff and water temperature. Climate change is expected to affect the extremes of the major river indices that impact fundamental ecological processes in river ecosystems. The available runoff and temperature data of rivers from three different hydrological regions of Lithuania were used. HBV software was applied for modelling of hydrological processes in the selected river catchments. The expected future ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The identified relationships between the response of intermittently flowing rivers and environmental factors highlight a threat of more severe conditions of flow regime due to potential anthropogenic pressures and projected climate changes in the future. Previous studies demonstrated an increase of climate aridity (Stonevičius et al, 2018) as well as a significant decrease of low flows in Lithuanian rivers (Šarauskienė et al, 2018) in the summer season at the end of the 21st century. All rivers in the studied Central Lithuanian hydrological region are at a high risk of increasing drying up in response to climate change.…”
Section: Discussionmentioning
confidence: 94%
“…The identified relationships between the response of intermittently flowing rivers and environmental factors highlight a threat of more severe conditions of flow regime due to potential anthropogenic pressures and projected climate changes in the future. Previous studies demonstrated an increase of climate aridity (Stonevičius et al, 2018) as well as a significant decrease of low flows in Lithuanian rivers (Šarauskienė et al, 2018) in the summer season at the end of the 21st century. All rivers in the studied Central Lithuanian hydrological region are at a high risk of increasing drying up in response to climate change.…”
Section: Discussionmentioning
confidence: 94%
“…The tolerant species ecological guild is used in many of fish-based methods of Central-Baltic European countries as a metric that increases with degradation of a river 46 . Taking into account the projected decrease in the flow of Lithuanian rivers in the future 12 , the impact of HPPs on fish can become even more adverse if the regulation of HPPs operation based on the current Q env definition will remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The results of study confirm that the correct establishment of e-flow is crucial in the environmentally friendly management of the run-of-river hydropower facilities. However, the summer low flows are expected to decrease, and the dry periods are likely to become more frequent in the future 12 . With limited water availability, ensuring energy production and suitable conditions for the maintenance of aquatic communities will be a challenge, as inflow into HPPs may become lower not only for the established e-flow but also for Q env .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of climate change on the hydrological regime of rivers are well studied. Due to changing precipitation and air temperature patterns in the Baltic Sea basin, alterations in the annual and seasonal runoff distribution are observed and they are projected to continue in the future [41][42][43][44][45]. The aforementioned major drivers result in higher winter runoff and lower runoff during other seasons.…”
Section: Discussionmentioning
confidence: 99%